Obtención de productos aromáticos con acción terapéutica a partir de las principales plantas medicinales de la provincia de El Oro - Calero Córdova, Yasser P. (2009)
Aromatic and medicinal plants that are found in a spontaneous manner in the area of Moro Moro in the province of El Oro are a natural resource that has great ecological values and a significant potential for local socio-economic development. Combining these positive factors, we could get to a situation of sustainable development, being able to cultivate these plants and getting some clear benefits, both economic and ecological.